(untitled) (Journal of Medical & Health Sciences Review, 2025)
Aim: This study aimed to evaluate the visual and anatomical outcomes following intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections in patients with diffuse diabetic macular edema (DME). The primary objective was to assess improvement in best-corrected visual acuity (BCVA) and reduction in central retinal thickness (CRT) as measured by spectral domain optical coherence tomography (OCT). Methods: A descriptive cross-sectional study was conducted at the Ophthalmology Department of Bahawal Victoria Hospital, Bahawalpur, over a six-month period. A total of 147 treatment-naïve patients aged 20–60 years with type 2 diabetes and diffuse DME confirmed by OCT (CRT ≥290 µm) were included. Participants received three monthly intravitreal anti-VEGF injections (bevacizumab, ranibizumab, or aflibercept). Visual acuity was assessed using Snellen’s chart and CRT was measured via OCT before treatment and two weeks after the third injection. The primary endpoint was defined as achieving both BCVA ≥20/40 and CRT ≤290 µm post-treatment. Secondary endpoints included changes in BCVA (in Snellen lines) and CRT (in micrometers). Data were analyzed using SPSS version 25.0. Results: Following three intravitreal anti-VEGF injections, there was a statistically significant improvement in both visual and anatomical outcomes. The proportion of patients achieving BCVA ≥20/40 increased from 12.2% pre-treatment to 48.3% post-treatment (p < 0.001), with a mean gain of 3.2 ± 1.5 Snellen lines. Mean CRT decreased significantly from 410.5 ± 45.6 µm at baseline to 287.3 ± 32.4 µm post-treatment (p < 0.001), with 65.3% of patients achieving CRT ≤290 µm. A combined outcome of improved BCVA and reduced CRT was achieved in 42.2% of patients. No major adverse events were reported, and transient intraocular pressure spikes occurred in 5% of cases. Conclusion: Intravitreal anti-VEGF therapy is effective in improving both visual acuity and reducing macular thickness in patients with diffuse diabetic macular edema. Early response to treatment, as assessed by OCT, can guide further management. While most patients benefit from anti-VEGF therapy, approximately 40% show partial or no improvement, highlighting the need for early identification of non-responders and consideration of alternative treatment strategies. Regular OCT monitoring and individualized treatment approaches are essential for optimizing long-term outcomes in patients with DME.